Strengthening Civic Values In Shaping The Character Of The Young Generation In The Digital Era - Devra, Desi Devrika (UNIVERSITAS PAKUAN, 2025)
This study explores the process of reinforcing civic values to shape the character of the younger generation in the digital era. It addresses the challenges posed by technological advancements such as misinformation, cyberbullying, and moral decline, emphasizing the urgent need for integrated educational strategies. Using a qualitative descriptive approach, the research investigates how collaboration between schools, families, and communities contributes to character development. Data were collected through literature review and semi-structured interviews with educators, students, and education observers. The findings reveal that civic education is more effective when supported by digital media and strengthened by consistent communication between parents and schools. Programs that integrate local values and national identity into digital learning platforms enhance students’ understanding of civic responsibility. Moreover, parental involvement through digital tools plays a significant role in reinforcing values taught at school. The study concludes that while digital platforms offer innovative methods for character education, their success depends on cultural relevance, ethical supervision, and equitable access. This research contributes to the development of character education models that are adaptable to technological changes while rooted in shared civic values, ensuring that students become both digitally competent and morally grounded individuals.